2015
DOI: 10.1016/j.psychres.2015.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Childhood maltreatment and social functioning in adults with sub-clinical psychosis

Abstract: Studies now acknowledge a robust association between childhood maltreatment and psychosis development in adulthood. Research shows that maltreatment not only influences the child's psychological wellbeing but also inhibits domains of social development. These social impairments have been found to predate the onset of psychosis and may crucially represent an intervening factor which triggers the decline towards psychosis. To examine social functioning as a potential mediating pathway between early maltreatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 50 publications
1
24
2
Order By: Relevance
“…One or two follow-up questions after the main probe question for each type of psychotic symptom were used to determine the severity of the symptoms. We used the strictest criteria to define the presence of psychotic symptoms in an attempt to capture clinically relevant psychotic symptoms [ 26 ]. The questions and response options required for the endorsement of each PLE were as follows:…”
Section: Methodsmentioning
confidence: 99%
“…One or two follow-up questions after the main probe question for each type of psychotic symptom were used to determine the severity of the symptoms. We used the strictest criteria to define the presence of psychotic symptoms in an attempt to capture clinically relevant psychotic symptoms [ 26 ]. The questions and response options required for the endorsement of each PLE were as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Pathway 4: feeling of loneliness Although only explored in four studies (Boyda & McFeeters, 2015;Jaya et al, 2017;Shevlin et al, 2015;Steenkamp et al, 2019), we found good evidence suggesting that a feeling of loneliness might mediate the CA-psychosis relationship. We could hypothesise that social withdrawal and loneliness may increase an individual's sensitivity to potential stressors in daily life restrict access to balanced information from the environment, maintaining biased cognitive biases.…”
Section: Pathway 3: Affective Pathwaymentioning
confidence: 67%
“…Recent metaanalyses by Varese et al (2012) and Bonoldi et al (2013) show a higher prevalence of child maltreatment among individuals diagnosed with a psychotic disorder, than within samples taken from the general population. Likewise, childhood maltreatment may also create a vulnerability to low-level psychotic experiences (PE), that is, in the absence of a clinical disorder (Bhavsar et al, 2017;Boyda & McFeeters, 2015;Sommer et al, 2010). Research shows that such experiences are transitory in about 80% of individuals, around 20% go on to develop persistent PE and 7% go on to develop a psychotic disorder, with an annual transition rate below 1% (Kaymaz et al, 2012;Linscott & van Os, 2013;Zammit et al, 2013).…”
Section: Introductionmentioning
confidence: 99%